Measurements of C2 and CH chemiluminescence of CH4/H2 flames by a digital camera - Kazuhiro YAMAMOTO; Wataru SAWADA (Journal of Thermal Science and Technology, 2024)
Since hydrogen does not emit carbon dioxide when it is burned, burning hydrogen directly is one option. However, as the hydrogen ratio in the total fuel increases, the visible flame emission becomes weaker. Therefore, when using fuels with hydrogen mixed with city gas, it is necessary to have a system that monitors incomplete combustion to ensure safe use of combustion equipment. In this study, we measured the C2 and CH chemiluminescence intensities of a laminar premixed flame of hydrogen and methane. These chemiluminescence intensities were evaluated using the ICCD camera, compared with flame images taken by the commercially available digital camera. Especially, we proposed a method to determine the C2 and CH chemiluminescence intensities simultaneously in terms of the signals composed of three primary colors of red (R), green (G), and blue (B) obtained by the digital camera images. The G signal of the flame obtained by the digital camera is almost proportional to the C2 chemiluminescence intensity. The B signal also shows a good linear relationship when data are divided into two groups according to the presence or the absence of the outer flame. We concluded that if the C2 and CH chemiluminescence intensities are predicted from the G signal and the B signal.